Healthcare ethics for Healthcare Practitioners - LATEGAN, LAETUS (UJ Press, 2017)
Healthcare ethics cannot be limited in scope to apply only to the patient but needs to apply to the healthcare practitioner as well. The relationship between the patient and the healthcare practitioner has shifted from a power relationship to a complementary relationship. Leadership, mentorship and coaching play important roles in facilitating this shift. Several themes informed this book on healthcare ethics: Vulnerability in healthcare ethics, Decisions between right and wrong, Quality of healthcare, Life-ending decisions, Community-based research, Ethical decision-making, Spritiuality in healthcare